French Involvement in the Greek War of Independence - Karakatsouli, Anna (Historein, 2022)
During the wars of the eighteenth century France lost most of its colonies. By 1821 the Restoration had also negated all the gains from Napoleon’s European expansion, meaning France could hardly be considered an imperial power. After 1823, however, it actively turned its focus to the Levant in order to regain a position of power. This article argues that France displayed extraordinary resilience in world politics. It managed to make major inroads into peripheral regions, such as Greece, and achieved considerable influence in the Mediterranean and an important degree of informal power. The article traces some highly diverse French projects and projections in the Eastern Mediterranean to better integrate French interventions in revolutionary Greece into the deployment of France’s global colonial ambitions.